Cortical and Subcortical Contributions to Neuroplasticity after Repetitive Transspinal Stimulation in Humans - Lynda M. Murray; Md. Anamul Islam; Maria Knikou (Neural Plasticity)
The objectives of this study were to establish cortical and subcortical contributions to neuroplasticity induced by noninvasive repetitive transspinal stimulation in human subjects free of any neurological disorder. To meet our objectives, before and after 40 minutes of transspinal stimulation we established changes in tibialis anterior (TA) motor-evoked potentials (MEPs) in response to paired transcranial magnetic stimulation (TMS) pulses at interstimulus intervals (ISIs) consistent with I-wave periodicity. In order to establish to what extent similar actions are exerted at the spinal cord and motor axons, changes in soleus H-reflex and transspinal evoked potential (TEP) amplitude following transspinal and group Ia afferent conditioning stimulation, respectively, were established. After 40 min of transspinal stimulation, the TA MEP consecutive peaks of facilitation produced by paired TMS pulses were significantly decreased supporting for depression of I-waves. Additionally, the soleus H-reflex and ankle TEP depression following transspinal and group Ia afferent conditioning stimulation was potentiated at intervals when both responses interacted at the spinal cord and nerve axons. These findings support the notion that repetitive transspinal stimulation decreases corticocortical inputs onto corticospinal neurons and promotes a surround inhibition in the spinal cord and nerve axons. This novel method may be a suitable neuromodulation tool to alter excitability at cortical and subcortical levels in neurological disorders.